2002
DOI: 10.1080/01443610120101664
|View full text |Cite
|
Sign up to set email alerts
|

Impact of asymptomatic maternal malaria parasitaemia at parturition on perinatal outcome

Abstract: A cross-sectional study involving 564 parturients who delivered singleton babies and 214 matched non-pregnant controls was carried out to determine the prevalence and impact of asymptomatic maternal malaria parasitaemia at parturition on the perinatal outcome. One hundred and forty (24.8%) parturients and 50 (23.4%) non-pregnant women were found to have asymptomatic malaria parasitaemia, respectively, while the congenital malaria rate in the neonates of the parasitaemic parturients was 0.7%. The incidence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 6 publications
8
24
0
Order By: Relevance
“…The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae. 19,24,25 In this study, higher parity did not confer any protection and this was consistent with the observations of Bako et al, 6 SuleOdu et al, 8 and Ofori et al 24 This finding was not surprising as same proportion of women across the various parities (nulliparous, primiparous and multiparous) used ITNs and also had at least 2 doses of IPT.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae. 19,24,25 In this study, higher parity did not confer any protection and this was consistent with the observations of Bako et al, 6 SuleOdu et al, 8 and Ofori et al 24 This finding was not surprising as same proportion of women across the various parities (nulliparous, primiparous and multiparous) used ITNs and also had at least 2 doses of IPT.…”
Section: Discussionsupporting
confidence: 81%
“…[6][7][8][9] Various studies have linked placental malaria to maternal anaemia. 18,24 However, in this study, there was no significant association between placental malaria and maternal anaemia when controlled for the other confounding variables, using the multivariate logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other reports in the 1980s however noted that the low reported incidence of congenital malaria particularly in Africa was surprising since malaria occurs more commonly in pregnancy (McGregor, 1983;Lehner & Andrews, 1988). More recently, findings from a number of studies from sub-Saharan Africa have described congenital malaria as a rare event largely because the prevalence of malaria parasite in cord blood or neonatal blood was very low and few newborns developed clinical disease during the first few weeks of life (Lamikanra 1993;Djibo & Cenac, 2000;Adachi et al, 2000;Sule-Odu et al, 2002). These studies had speculated that the effectiveness of the placenta to restrain the malaria parasite passage to the foetus and the remarkable capacity of the foetus to resist infection as demonstrated by Miller & Telford (1997) was responsible for the rarity of congenital malaria.…”
Section: Congenital Malaria: Rare or Frequent Eventmentioning
confidence: 99%